2014
DOI: 10.1589/jpts.26.1729
|View full text |Cite
|
Sign up to set email alerts
|

The Reference Values for the Chair Stand Test in Healthy Japanese Older People: Determination by Meta-analysis

Abstract: [Purpose] The aim of this study was to determine the reference values for the chair stand test (CST) in healthy older Japanese people. [Methods] Relevant research articles for the 5-repetition chair stand test (CS-5) and the 30-second chair stand test (CS-30) were identified by electronic database and manual searching. Research articles involving healthy Japanese people aged 60 years and older were included in a meta-analysis. Weighted means of the CS-5 and CS-30 were estimated by the random effect model as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 24 publications
3
43
0
2
Order By: Relevance
“…The search terms used were ''hand grip strength/akuryoku,'' ''hand strength,'' ''grip,'' ''grasp,'' ''strength,'' ''power,'' ''older people/koureisya,'' ''aged,'' and ''elderly'' in appropriate combinations. The selection criteria for papers used in the meta-analysis were set as follows in accordance with earlier studies [12][13][14][15]: (1) papers written in Japanese or English; (2) papers on Japanese community-dwelling people aged C60 years old; (3) papers on community-dwelling elderly independent in activities of daily living (ADLs); (4) papers not examining frail elderly or elderly with an evident disease; (5) papers reporting measurements in kilograms or Newtons; (6) papers reporting data on hand grip strength by sex; and (7) papers listing the number of subjects and the mean and standard deviation (SD) of hand grip strength. Four researchers (NK, RK, TN, and MA) held discussions to determine search terms to use and which papers to include in the analysis.…”
Section: Paper Retrieval Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The search terms used were ''hand grip strength/akuryoku,'' ''hand strength,'' ''grip,'' ''grasp,'' ''strength,'' ''power,'' ''older people/koureisya,'' ''aged,'' and ''elderly'' in appropriate combinations. The selection criteria for papers used in the meta-analysis were set as follows in accordance with earlier studies [12][13][14][15]: (1) papers written in Japanese or English; (2) papers on Japanese community-dwelling people aged C60 years old; (3) papers on community-dwelling elderly independent in activities of daily living (ADLs); (4) papers not examining frail elderly or elderly with an evident disease; (5) papers reporting measurements in kilograms or Newtons; (6) papers reporting data on hand grip strength by sex; and (7) papers listing the number of subjects and the mean and standard deviation (SD) of hand grip strength. Four researchers (NK, RK, TN, and MA) held discussions to determine search terms to use and which papers to include in the analysis.…”
Section: Paper Retrieval Methodsmentioning
confidence: 99%
“…To set reference values for hand grip strength that can be adapted to Japanese people, data from a large sample obtained from a wide geographic area are needed. Thus far, we have used metaanalysis to integrate research data from various areas to more accurately set reference values for several motor function tests such as the Timed Up and Go test [12][13][14][15]. The aim of this study was to calculate reference values for hand grip strength in independent Japanese communitydwelling elderly using meta-analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The CS-5 has been demonstrated to be a simple and viable physical performance to request a decrease in daily living activity (ADL) and falls in the elderly (47,48,49) . Nakazono et al (50) , concluded that CS-5 and Chair Test (30 seconds) are simple and viable physical performance tests for the elderly and rehabilitation patients in the clinical context, to evaluate their muscular endurance.…”
Section: Discussionmentioning
confidence: 99%
“…In taking the test, the participants were instructed to rise from a chair (which was 46 centimeters high and armless) to a full standing position and then return to a seated position as quickly as possible for ve repetitions. Each participant performed the test two times [20,21]. The best performance in terms of the total time taken for all ve repetitions (that is, the shortest time) was used for our analysis.…”
Section: Lower-extremity Performance Measuresmentioning
confidence: 99%